Development and Validation of a Scale to Assess the Factors Contributing towards School - Faseeha Khursheed,Attiya Inam, Muhammad Abiodullah, (PJE, 2023)
School refusal behavior is a serious issue in Pakistan which has remained unnoticed. To understand the intensity of the issue, it is important to understand the school-related factors for school refusal. There was no tool available to study these factors in cultural context of Pakistan